Thrombin Promotes Macrophage Polarization into M1-Like Phenotype to Induce Inflammatory Responses - López-Zambrano, Mercedes; Rodriguez-Montesinos, Julián; Crespo-Avilan, Gustavo E.; Muñoz-Vega, Mónica; Preissner, Klaus T. (Thrombosis and Haemostasis, 2020)
Despite strong evidence supporting the cellular interplay between haemostasis and innate immunity, humoral connections between blood coagulation and the behavior of inflammatory macrophages are not well understood. In this study, we investigated changes in gene expression of selected cytokines and chemokines and their secretion profiles following thrombin stimulation of murine macrophages. Thrombin promoted differentiation of macrophages into an M1-like phenotype that was associated with the expression of classical pro-inflammatory markers. The cellular actions of thrombin on macrophages were mediated in part by protease-activated receptor-1 (PAR-1) and were dependent on phosphoinositide 3-kinase/AKT and nuclear factor-κB. Moreover, heat-denatured thrombin stimulated the secretion of some pro-inflammatory mediators to the same magnitude indicating that different receptors transmit cellular signals of enzymatically active thrombin and nonactive thrombin, the latter remaining so far undefined. Finally, pretreatment of macrophages with thrombin resulted in tolerance against secondary stimulation by lipopolysaccharide with regard to expression of tumor necrosis factor-α. These results provide new insights into the molecular link between the key enzyme of haemostasis and innate immunity responses.
Keywords: thrombin receptors; tumor necrosis factor-α; protease-activated receptors; cytokine profile; innate immunity